2005
DOI: 10.6090/jarq.39.109
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Damping-Off of Tomato Seedlings and Cucumber Phomopsis Root Rot by Bacillus subtilis RB14-C

Abstract: Bacillus subtilis RB14-C, which is a streptomycin resistant mutant of B. subtilis RB14 isolated from compost, produces an antifungal peptide, iturin A, and was evaluated for its suppressive ability against damping-off of tomato seedlings and Phomopsis root rot of cucumber. In damping-off disease of tomato seedlings caused by Rhizoctonia solani, RB14-C cell suspension treatment did not suppress the disease occurrence whereas germinated seed treatment of the RB14-C cells reduced the occurrence of the damping-off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Studies on the effect of ethyl acetate extract on mycelial weight, pycnidial number and germ tube length of the pathogen revealed that both bacterial extracts were highly effective in suppressing growth of the pathogen. Biological control activity of B. subtilis and Pseudomonas spp., against several Phomopsis species was reported (Cubeta et al 1985;Fuchs and Defago 1991;Kita et al 2005;Maurhofer et al 1992). P. aeruginosa was employed as active biocontrol agent against many plant pathogens (Anjaiah et al 2003;Krishna Kishore et al 2005;Siddique and Ehteshamul-Haque 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effect of ethyl acetate extract on mycelial weight, pycnidial number and germ tube length of the pathogen revealed that both bacterial extracts were highly effective in suppressing growth of the pathogen. Biological control activity of B. subtilis and Pseudomonas spp., against several Phomopsis species was reported (Cubeta et al 1985;Fuchs and Defago 1991;Kita et al 2005;Maurhofer et al 1992). P. aeruginosa was employed as active biocontrol agent against many plant pathogens (Anjaiah et al 2003;Krishna Kishore et al 2005;Siddique and Ehteshamul-Haque 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, lipopeptides produced mainly by Bacillus species are very popular as antifungal agent to suppress plant tomato disease development (Ongena and Jacques 2008). Kita et al (2005) discussed the suppressive ability of iturin A produced by B. subtilis RB14-C against the dampingoff of tomato seedlings caused by R. solani and Phomopsis root rot of cucumber. A mycosubtilin from a B. subtilis overproducing strain was effective for reducing a Pythium infection of tomato seedlings marked by a significant increase in the germination rate of seeds with a greater fresh weight of emerging seedlings (Leclère et al 2005).…”
Section: Second Week First Weekmentioning
confidence: 99%
“…Also,Kita et al (2005) evaluated the suppressive ability of iturin A isolated from B. subtilis RB14 against damping-off of tomato seedlings and Phomopsis root rot of cucumber. Biosurfactant-type lipopeptides are involved in the multifaceted biocontrol potential of B. subtilis species against fungi spread and infection.…”
mentioning
confidence: 99%
“…TheAspergillus spp. and Biopolaris sorokiniana enabling its use as biocontrol agent[157].Kita et al [158]. discussed the suppressive ability of Iturin A produced by B. subtilis RB14-C against the damping-off of tomato seedlings caused by R. solani and Phomopsis root rot of cucumber.…”
mentioning
confidence: 99%